2004
DOI: 10.1111/j.1467-7652.2004.00086.x
|View full text |Cite
|
Sign up to set email alerts
|

Bt rice harbouring cry genes controlled by a constitutive or wound‐inducible promoter: protection and transgene expression under Mediterranean field conditions

Abstract: SummarySeven homozygous transgenic lines of two European commercial cultivars of rice (Ariete (A) and Senia (S)), harbouring the cry1B or cry1Aa Bacillus thuringiensis ( Bt ) δ -endotoxin genes, were field evaluated for protection from striped stem borer (SSB) ( Chilo suppressalis ) of protection, with a notably low level of penetration of SSB larvae in the stems, but higher external symptoms than constitutive lines, probably due to the time lag to benefit from the protective effect of Cry1B.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(46 citation statements)
references
References 40 publications
4
40
0
2
Order By: Relevance
“…Low copy of the integration of the transgene may be considered as good result, since several studies show the positive correlation between high copy number of transgenes and cytosine methylation mediated silencing (Kohli et al 1996;Lechtenberg et al 2003;Matzke and Matzke 1995). Western blotting also reconfirmed the proper integration and expression of cry1Ab gene in the transgenic plants, however, we found smaller fragments that reacted with Cry1Ab antibody in leaf extracts of transgenic plants could be due to protein degradation by intrinsic leaf proteases (Australia New Zealand Food Authority (ANZFA) 2001) or degradation of protein during sample preparation (Breitler et al 2004;Cheng et al 1998;Fujimoto et al 1993;Lachance et al 2007). CryIAb levels in transgenic plants was estimated to be about 0.1% of total soluble leaf proteins by comparing with Bt protoxin as standard.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Low copy of the integration of the transgene may be considered as good result, since several studies show the positive correlation between high copy number of transgenes and cytosine methylation mediated silencing (Kohli et al 1996;Lechtenberg et al 2003;Matzke and Matzke 1995). Western blotting also reconfirmed the proper integration and expression of cry1Ab gene in the transgenic plants, however, we found smaller fragments that reacted with Cry1Ab antibody in leaf extracts of transgenic plants could be due to protein degradation by intrinsic leaf proteases (Australia New Zealand Food Authority (ANZFA) 2001) or degradation of protein during sample preparation (Breitler et al 2004;Cheng et al 1998;Fujimoto et al 1993;Lachance et al 2007). CryIAb levels in transgenic plants was estimated to be about 0.1% of total soluble leaf proteins by comparing with Bt protoxin as standard.…”
Section: Discussionsupporting
confidence: 61%
“…This level of protein accumulation of synthetic endotoxin genes under the control of a constitutive promoter was relatively acceptable as compared with those reported in other transgenic plants which typically ranged from 0.002% (Tu et al 2000) to 0.4-0.5% of total soluble protein (Breitler et al 2004;Jansens et al 1997;Koziel et al 1993;Wu et al 2002). The accumulation of the recombinant endotoxin at 0.002-0.005% of total soluble protein has been shown to be sufficient for biological effect (Breitler et al 2004;Vaeck et al 1987). Ghareyazie et al (1997) reported the accumulation of 0.1% synthetic Cry1Ab protein in transgenic rice plants by using the same synthetic cry1Ab gene as used in our study with tissue-specific promoter.…”
Section: Discussionmentioning
confidence: 87%
“…S. biformis feeds on young plants by lacerating the green tissue of leaves, and outbreaks have often been reported in China, India, and Bangladesh (Nugaliyadde and Heinrichs 1984, Dale 1994, Pathak and Khan 1994. Since the 1990s, numerous rice genotypes expressing various insect-active crystal (Cry) proteins derived from the bacterium Bacillus thuringiensis Berliner (Bt) (referred as Bt rice hereafter) have been developed with resistance to one or more rice lepidopterous pests, the most important of which are the yellow stem borer, Scirpophaga incertula (Walker) (Lepidoptera: Pyralidae), the striped stem borer, Chilo suppressalis (Walker) (Lepidoptera: Crambidae), and the leaffolder, Cnaphalocrocis medinalis (Guené e) (Lepidoptera: Pyralidae) (reviewed by Breitler et al 2004, High et al 2004, Ramesh et al 2004, Riaz et al 2006, Tang et al 2006, Rahman et al 2007. Since the late 1990s, Þeld trials of various Bt rice genotypes expressing Cry1Ab protein (Shu et al 2000;Ye et al 2001aYe et al , 2003, a fusion protein of Cry1Ab/Cry1Ac (Ye et al 2001b), Cry2A, Cry1Ac, and Cry9C , Cry1C (Tang et al 2006), and a fusion protein of Cry1Ac/CpTI (Han et al 2007) have been conducted in China.…”
Section: Abstract Bt Rice Nontarget Insect Rice Thrip Stenchaetotmentioning
confidence: 99%
“…Results of recent field trials in both locations showed significant resistance against target insects, i.e. YSB and RLF (Breitler et al, 2004;Bashir et al, 2005;Mahmood-ur-Rahman et al, 2007, 2014a, 2014bTabashnik et al, 2009) (Table 2). The rice plants were artificially infested ( Figures 1A-1C) with the target insects and their attack was measured quantitatively.…”
Section: Insect-resistant Ricementioning
confidence: 92%
“…Insect-resistant Bt rice has also been produced in Pakistan (Mahmood-ur-Rahman et al, 2007) and in the Mediterranean region (Breitler et al, 2004). Results of recent field trials in both locations showed significant resistance against target insects, i.e.…”
Section: Insect-resistant Ricementioning
confidence: 99%